Introduction to speechwork for actors an inclusive approach - Carlos, Ron (London, UK Methuen Drama, 2023)
"Traditional speech work has long favoured an upper-class white accent as the model of intelligibility. Because of that, generations of actors have felt disconnected from their own identities and acting choices. This much-needed textbook redresses that trend and encourages actors to achieve intelligibility through rigorous language analysis andan exploration of their own accent and articulation practices. It breaks down a process for analyzing text in a way that excites the imagination, offering a number of exercises that bring awareness to each actor to make their own speech come alive. Guiding the student through the labyrinth of abstract concepts and terms, readers are delivered into the practicality of exercises and explorations. Informed throughout by notes from directors and acting teachers, as well as the author's own extensive experience, this book serves as an ideal speech-training resource for the 21st Century actor, and includes specially commissioned online videos demonstrating key exercises"--Provided by publisher.
A snapshot of you -- Meet your text -- Language of your body -- Color me aware -- The work of awareness -- The shape of your sound -- Your own kind of music -- River of sounds -- Splashing in the river -- Moving forward.
Includes bibliographical references.
Keywords: Voice culture; Speech; Acting